Konsep Umat Dalam Al-Quran : Menggali Nilai-Nilai Apriori Dan Aposteriori Sosial - Fauzi, Ammar (Sekolah Tinggi Filsafat Islam Sadra, 2015)
AbstrakAlthough umat (ummah) has been standarized in the Indonesian vocabulary and will be easily found in the Qurâan, it seems that this term has not been commonly and uniquely emerging in the sociology and politics literatures in Bahasa Indonesia. As far as common sense and lexical meaning, the term of umat ordinarily connotes a kind of religious belief. However, how the concept of umat should be described in the view of the Quran? This paper examines that the islamic faith and thought could be an element that capture the diversity and differences of Muslim people into a core, i.e. the one umat (community) in its typical and complete sense encompassing a priori and a posteriori values.Keywords: umat, leader, individu, social, fitrah, self-knowing, a priori, a posteriori Â AbstrakMeskipun umat (ummah) telah terbakukan dalam Bahasa Indonesia dan akan dengan mudah dite-mukan dalam Al-Quran, tampaknya istilah ini belum secara umum dan unik muncul dalam literatur sosiologi dan politik Bahasa Indonesia. Sejauh pengertian umum dan makna leksikal, istilah umat biasanya berkonotasi dengan semacam keyakinan agama. Namun, bagaimana konsep umat itu sendiri dapat dijelaskan dalam pandangan Al-Quran? Makalah ini akan menimbang bagaimana keimanan dan pemikiran Islam bisa menjadi elemen yang merangkul keragaman dan perbedaan orang Muslim ke dalam satu inti, yaitu umat yang satu dalam artinya yang khas dan lengkap hingga meliputi nilai-nilai apriori dan aposteriori.Kata-kata kunci: umat, pemimpin, individu, sosial, fitrah, mengenal-diri, apriori, aposteriori